Reactive power dispatch for cost and loss minimization in power system during line outage contingency by using MAIEP / Farid Fakhri Ismail - Ismail, Farid Fakhri (2010)
Electrical power system are designed and operated to meet the continuous variation of power demand. The optimal reactive power dispatch is to optimize the steady state performance of a power system in terms of one or more objective functions while fulfilling both equality and inequality constrains. This paper present a new optimization technique termed as Multi Agent Immune Evolutionary Programming (MAIEP) utilizing Reactive Power Dispatch (RPD) to minimize total generation cost and losses in power system. MAIEP concept is origin from few combinations of optimization technique of Multiagent System (MAS), Artificial Immune System (AIS) and Evolutionary Programming (EP) optimization technique. In a large power system network, there are many possibilities of the contingency occurrence. Contingencies could be line outage, the occurrence of contingency in a nominal voltage and leads to voltage collapse. Line outage could be extreme case when the outage line involving any units of the power supply in the system. The programming codes are written in MATLAB. The propose technique was tested using IEEE-26-Bus Reliability Test System. The result obtained from before contingency and during contingency are comparing with MAIEP optimization technique and pre optimization technique.